Divergence of neuroimmune circuits activated by afferent and efferent vagal nerve stimulation in the regulation of inflammation. (4th February 2021) - Murray, Kaitlin; Rude, Kavi M.; Sladek, Jessica; Reardon, Colin
Abstract : Key points: It has previously been shown that afferent and efferent vagal nerve stimulation potently inhibits lipopolysaccharide (LPS)‐induced inflammation Our data show inhibition of inflammation by efferent but not afferent vagal nerve stimulation requires T‐cell derived acetylcholine We show that afferent and efferent neuroimmune circuits require β2 ‐adrenergic receptor signalling Abstract: Chronic inflammation due to inappropriate immune cell activation can have significant effects on a variety of organ systems, reducing lifespan and quality of life. As such, highly targeted control of immune cell activation is a major therapeutic goal. Vagus nerve stimulation (VNS) has emerged as a therapeutic modality that exploits neuroimmune communication to reduce immune cell activation and consequently inflammation. Although vagal efferent fibres were originally identified as the primary driver of anti‐inflammatory actions, the vagus nerve in most species of animals predominantly comprises afferent fibres. Stimulation of vagal afferent fibres can also reduce inflammation; it is, however, uncertain how these two neuroimmune circuits diverge. Here we show that afferent VNS induces a mechanism distinct from efferent VNS, ameliorating lipopolysaccharide (LPS)‐induced inflammation independently of T‐cell derived acetylcholine (ACh) which is required by efferent VNS. Using a β2 ‐adrenergic receptor antagonist (β2 ‐AR), we find that immune regulation induced by intact, afferent, or efferent VNS occurs in a β2‐ AR‐dependent manner. Together, our findings indicate that intact VNS activates at least two distinct neuroimmune circuits each with unique mechanisms of action. Selective targeting of either the vagal efferent or afferent fibres may provide more personalized, robust and effective control over inappropriate immune responses. Key points: It has previously been shown that afferent and efferent vagal nerve stimulation potently inhibits lipopolysaccharide (LPS)‐induced inflammation Our data show inhibition of inflammation by efferent but not afferent vagal nerve stimulation requires T‐cell derived acetylcholine We show that afferent and efferent neuroimmune circuits require β2 ‐adrenergic receptor signalling